2015
DOI: 10.1515/jogs-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of precipitable water over Ghana using GPS signals and reanalysis products

Abstract: Signals from Global Navigational Satellite Systems (GNSS) when integrated with surface meteorological parameters can be used to sense atmospheric water vapour. Using gLAB software and employing precise point positioning techniques, zenith troposphere delays (ZTD) for a GPS base station at KNUST, Kumasi have been computed and used to retrieve Precipitable Water (PW). The PW values obtained were compared with products from ERA-Interim and NCEP reanalysis data. The correlation coefficients, r, determined from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Przykładem takiego oprogramowania jest aplikacja nawigacja gLAB stosowana do pozycjonowania satelitarnego GNSS w trybie post-processing [16]. Program gLAB (GNSS-Lab Tool) jest powszechnie stosowany w pozycjonowaniu statycznym GNSS [10], pozycjonowaniu kinematycznym GNSS [12], monitoringu stanu troposfery [1] itp. Program gLAB ma szero-kie spektrum zastosowania badawczego, w tym także może być wykorzystywany w nawigacji lotniczej do odtworzenia pozycji statku powietrznego.…”
Section: Wprowadzenieunclassified
“…Przykładem takiego oprogramowania jest aplikacja nawigacja gLAB stosowana do pozycjonowania satelitarnego GNSS w trybie post-processing [16]. Program gLAB (GNSS-Lab Tool) jest powszechnie stosowany w pozycjonowaniu statycznym GNSS [10], pozycjonowaniu kinematycznym GNSS [12], monitoringu stanu troposfery [1] itp. Program gLAB ma szero-kie spektrum zastosowania badawczego, w tym także może być wykorzystywany w nawigacji lotniczej do odtworzenia pozycji statku powietrznego.…”
Section: Wprowadzenieunclassified
“…Lack of meteorological sensors attached to NIGNET and the poor resolution of NCEP/DOE was attributed to the weak correlation. In Ghana, Acheampong et al (2015) found a correlation of more than 60% when PWV from GNSS was compared with that from the NCEP/DOE Reanalysis II. The study of Isioye et al (2017) capitalized on the NIGNET to study spatio-temporal variability of PWV.…”
Section: Introductionmentioning
confidence: 97%
“…e results showed that GNSS-PWV provides a useful source of humidity information which can be utilised to improve the water cycle in numeric weather models (NWMs) for various applications in Nigeria. Furthermore, as means of enhancing PWV retrieval from GNSS ground-based receivers in West Africa, Isioye et al [28] [29] comparatively studied PWV estimation using GNSS observations in Ghana and datasets from ERA-Interim and NCEP reanalysis. e study demonstrated that PWV can be obtained with high precision from GNSS signals in Ghana.…”
Section: Introductionmentioning
confidence: 99%